2005
DOI: 10.1007/s00134-005-2652-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of inflammatory responses by FC-77, a perfluorochemical, in lipopolysaccharide-treated RAW 264.7 macrophages

Abstract: FC-77 inhibits inflammatory responses in LPS-stimulated macrophages by a mechanism that involves the attenuation of NF-kappaB dependent induction of COX-2/PGE2 pathway and the pro- /anti-inflammatory cytokine ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
23
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 23 publications
4
23
0
Order By: Relevance
“…Then, active NF-κB translocates into the nucleus and triggers an induction of iNOS and pro-inflammatory cytokines (26,28). In the present study, we also found that treatment with FC-77 prevented LPS-induced IκB-α degradation in the cytoplasm and NF-κB activation in nuclei, which is similar to our previous study (11). The result further indicates that inhibition of NF-κB activation by FC-77 may be an important mechanism accounting for the suppression of iNOS expression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Then, active NF-κB translocates into the nucleus and triggers an induction of iNOS and pro-inflammatory cytokines (26,28). In the present study, we also found that treatment with FC-77 prevented LPS-induced IκB-α degradation in the cytoplasm and NF-κB activation in nuclei, which is similar to our previous study (11). The result further indicates that inhibition of NF-κB activation by FC-77 may be an important mechanism accounting for the suppression of iNOS expression.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to the improvements in pulmonary physiology, an anti-inflammatory activity of perflubron due to inhibition of the production of reactive oxygen species (ROS) and pro-inflammatory cytokines (7 -10) was reported, which may account for its beneficial effect in acute lung injury. Importantly, our previous study demonstrated that FC-77 reduced prostaglandin E 2 formation and cycloxygenase-2 induction in endotoxin-treated macrophages (11). Accordingly, we propose that FC-77 may exhibit an antiinflammatory activity.…”
Section: Introductionmentioning
confidence: 56%
“…In addition to its ability for carrying and dissolving high levels of oxygen, PFC has shown anti-inflammatory properties both in vivo and in vitro [11,12]. However, the molecular mechanisms regarding the possible effects of PFC on decreasing sustained inflammation in ARDS have not been elucidated.…”
Section: Introductionmentioning
confidence: 98%
“…inhibition of inducible nitric oxide synthase, suppression of the COX2-PGE 2 pathway), and we cannot exclude that they have contributed to the observed effects in our study. 37,38 The oxygenation-and anti-inflammatory capacity of PFCs has led to their pre-clinical and clinical evaluation in numerous pathological conditions including shock, brain injury, anemia and cardiac disease. 39 As far as the authors are aware, the present study is the first report on the successful use of PFCs in inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 99%